Geophysics and trial trenches (Scottish Historical and Archaeological Internet Reports, 2001)
With the exception of trenches 1 and 2, all excavated areas produced evidence of in situ archaeological deposits over a wide area. It appears from trenches 4-6 that the whole of the east-facing slope is artificially modified for arable purposes, but that most of this landscaping occurred after the abbey was abandoned. In general, the potential medieval features found in trenches 5 and 6 reflected attempts to create dry and stable building platforms, most likely for timber buildings, and probably associated with the earliest monastic colonisation of the site.